Photocatalytic degradation of geosmin by titanium dioxide powder synthesized by the hydrothermal route - Pusit Pookmanee (2018)
Titanium dioxide powder was synthesized by the hydrothermal route with the starting precursors as titanium isopropoxide, ammonium hydroxide and nitric acid. The final of pH value of mixed solution was 1 and treated in the hydrothermal PTFE vessel at 80-100 °C for 3h. The phase of titanium dioxide was characterized by X-ray diffractometer (XRD). The morphology of titanium dioxide was investigated by scanning electron microscope (SEM). The chemical composition of titanium dioxide was examined by energy dispersive X-ray spectrophotometer (EDXS). The photocatalytic degradation of geosmin by titanium dioxide was determined by gas chromatograph coupled with flame ionization detector (GC-FID). © (2010) Trans Tech Publications.